Writing to Cuba : filibustering and Cuban exiles in the United States - Lazo, Rodrigo (Envisioning Cuba., 2005)
A study of the exiled Cuban writers from the 19th century known as los filibusteros who created a body of literature demanding independence from Spain and alliance with or annexation to the US. The transnational culture of writers went hand in hand with economic flow between the countries and was fuelled by belief in a US promise of freedom.